The Impact of Arabic Language and Script on the Medieval Architectural Heritage of Tashkent - Bakirov, Poyan; Karimov, Nodir; Yusubov, Jaloliddin; Aripova, Yelena; Turaev, Laziz; Shomusarov, Shorustam; Torgautova, Sholpan (Architecture Image Studies, 2024)
This paper examines the profound and influential role of the Arabic language and its distinctive script in shaping the architectural and cultural significance of medieval structures in Tashkent. With the arrival of Islam in the 8th century, Arabic became the main vehicle for scholarly, religious, and administrative communication, leaving an indelible mark on the region’s architectural heritage. Iconic landmarks such as the Barakhan Madrasah and Kukaldosh Madrasah boast intricate Arabic inscriptions, including Quranic verses, prayers, and other significant religious texts in the elegant Kufic and Naskh calligraphic styles. These delicately crafted inscriptions give spiritual depth and artistic sophistication to these structures. Besides, Arabic script inspired the development of ornamental designs that gave a peculiar character to the medieval architecture of Tashkent. This analysis has shown that the Arabic influence on the region extends deep into the realms of visual and cultural representation and underlines its persistence.